1999
DOI: 10.1021/jm9805541
|View full text |Cite
|
Sign up to set email alerts
|

Novel Antidiabetic and Hypolipidemic Agents. 5. Hydroxyl versus Benzyloxy Containing Chroman Derivatives

Abstract: Several thiazolidinediones having chroman moieties were synthesized and evaluated for their euglycemic and hypolipidemic activities. Some of the analogues having an aminoalkyl group as a linker between the chroman ring and 4-[5-(2,4-dioxo-1, 3-thiazolidinyl)methyl]phenoxy moiety seem to be better than troglitazone. In vitro transactivation assays of PPARgamma have been carried out with these glitazones to understand their molecular mechanism. For the first time we have found that some of the unsaturated thiazo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 38 publications
1
26
0
Order By: Relevance
“…On the other hand, it has been reported that protection of the hydroxyl group in the chroman ring of TGZ with benzyl retains its euglycemic and hypolipidemic activities in vivo. 19 This fact, together with the observation that tocopherol moiety alone does not induce physiological response similar to TGZ in HCT-116 cells, 10 suggests that the modification of the hydroxyl group in the chroman moiety would be well tolerated. To ensure a large conformational freedom of the bioactive TGZ motif, a poly(ethylene glycol) (PEG) linker with rational length was introduced to link it with the biotin tag.…”
Section: Design and Synthesis Of Tgz-biotinmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, it has been reported that protection of the hydroxyl group in the chroman ring of TGZ with benzyl retains its euglycemic and hypolipidemic activities in vivo. 19 This fact, together with the observation that tocopherol moiety alone does not induce physiological response similar to TGZ in HCT-116 cells, 10 suggests that the modification of the hydroxyl group in the chroman moiety would be well tolerated. To ensure a large conformational freedom of the bioactive TGZ motif, a poly(ethylene glycol) (PEG) linker with rational length was introduced to link it with the biotin tag.…”
Section: Design and Synthesis Of Tgz-biotinmentioning
confidence: 99%
“…20 Preparation of the probe was commenced with (R/S)-Trolox. 19 Reduction of the carboxyl acid group with LiAlH 4 yielded 1, which was then attached with the PEG linker to give 2. Reaction of 2 with 4-fluorobenzaldehyde afforded 3 with low yield, owing to partially denatured KOBu-t. Aldol reaction of 3 with thiazolidine-2,4-dione gave 4, which was reduced with MeOH-Mg to furnish 5 as a mixture of two diastereomer pairs (2R-5R/2S-5S and 2R-5S/2S-5R).…”
Section: Design and Synthesis Of Tgz-biotinmentioning
confidence: 99%
See 1 more Smart Citation
“…Thiazolidinediones have been shown to improve insulin sensitivity/glucose utilization in animal model and to enhance insulin sensitivity in human. [26][27][28][29] But, it was assumed that troglitazone has the hepatotoxicity [30][31][32] due to the enterohepatic circulation of the metabolites, that is quinone moiety.In order to prevent this and to discover novel compounds which have the ability to increase glucose utilization, we focused our attention on the modification of chroman moiety to erythrose, ribose and substituted pyrrolidine group. As a result of our efforts, in this paper, we describe the synthesis and the in vitro glucose utilization activity.…”
mentioning
confidence: 99%
“…Thiazolidinediones have been shown to improve insulin sensitivity/glucose utilization in animal model and to enhance insulin sensitivity in human. [26][27][28][29] But, it was assumed that troglitazone has the hepatotoxicity [30][31][32] due to the enterohepatic circulation of the metabolites, that is quinone moiety.…”
mentioning
confidence: 99%